The effect of access to information and communication technology on household labor income: Evidence from one laptop per child in Uruguay - Joaquin Marandino; Phanindra V. Wunnava (Economies, 2017)
This paper examines the effect of the One Laptop Per Child program in Uruguay (Plan Ceibal) on household labor income. Since 2007, the Uruguayan government has delivered one laptop to every child and teacher in public primary schools. This program has considerably increased access to information technology within households, as evidenced by parents' utilization of said technology. Households in the department of Florida received laptops in 2007, while those in the department of Canelones received them in 2009. Therefore, using data from Household Surveys from the National Institute of Statistics in Uruguay, a difference-in-difference model is estimated to capture the effect of the plan of giving laptops on labor income. The results indicate that there is a statistically significant positive effect of the plan on household labor income for households below median income, specifically, those at the 10th and 20th quantiles. Such findings suggest that the program has greater potential when targeted to low-income households, where parents possess lower computer skills.
Keywords: H41; H52; J31; O33; 330; technology; laptop; Uruguay; labor income; difference-in-difference; median income; quantile regression; propensity-score matching